Vitamin D levels and bone mass in rheumatoid arthritis - Brance, María Lorena (2015)
Rheumatoid arthritis (RA) is a chronic systemic inflammatory autoimmune disease with high prevalence of osteoporosis. Previous evidence indicates an association between vitamin D deficiency and autoimmune diseases. The aim of this study was to evaluate serum 25 hydroxyvitamin D [25(OH)D] levels, bone mineral density (BMD) and disease activity in RA patients living in Argentina. We studied 34 RA women and 41 healthy women as a control group. RA patients had lower 25(OH)D levels (20.4 ± 0.9 ng/ml) than controls (26.3 ± 1.9 ng/ml; p < 0.05). No significant differences were found in lumbar spine BMD between premenopausal (preM) or postmenopausal (postM) patients, but femoral neck BMD was significantly lower in postM RA patients (T score −2.5 ± 0.4) than in postM control subjects (T score −0.9 ± 0.3, p = 0.014). Although no linear correlation between 25(OH)D levels and disease activity (DAS-28) was found, patients with moderate-high disease activity had lower 25(OH)D levels than those with low disease activity: DAS-28 >3.2: 19.5 ± 0.88 ng/ml; DAS-28 ≤3.2: 23.7 ± 2.8 ng/ml (p = 0.047). After 1 year of vitamin D treatment 25(OH)D levels were increased while DAS-28 were decreased (n = 25; p < 0.05). We conclude that patients with RA had lower 25(OH)D levels than the control group. Low levels of 25(OH)D were associated with moderate-high disease activity suggesting the importance of optimal 25(OH)D levels in RA patients. Femoral neck BMD was lower in postM RA patients. No differences in lumbar BMD were found between preM and postM RA patients, suggesting that bone mass evaluation in RA patients should include femoral neck BMD regardless of age.